Investigation of Genipin Cross-Linked Microcapsule for Oral Delivery of Live Bacterial Cells and Other Biotherapeutics: Preparation and In Vitro Analysis in Simulated Human Gastrointestinal Model - Hongmei Chen; Wei Ouyang; Christopher Martoni; Fatemeh Afkhami; Bisi Lawuyi; Trisna Lim; Satya Prakash (International Journal of Polymer Science)
Oral therapy utilizing engineered microorganisms has shown promise in the treatment of many diseases. By microencapsulation, viable cells can overcome the harsh gastrointestinal (GI) environment and secrete needed therapeutics into the gut. These engineered cells should be encased without escaping into the GI tract for safety concerns, thus robust microcapsule membrane is requisite. This paper examined the GI performance of a novel microcapsule membrane using a dynamic simulated human GI model. Results showed that the genipin cross-linked alginate-chitosan (GCAC) microcapsules possessed strong resistance to structural disintegration in the simulated GI environment. Leakage of encapsulated high molecular weight dextran, a model material to be protected during the simulated GI transit, was negligible over 72 h of exposure, in contrast to considerable leakage of dextran from the non-cross-linked counterparts. These microcapsules did not alter the microflora and enzymatic activities in the simulated human colonic media. This study suggested the potential of the GCAC microcapsules for oral delivery of live microorganisms and other biotherapeutics.